پیغمبر اسلامﷺکی نبوت ورسالت پراعتراض(بشریت نبوت ورسالت کے منافی ہے):ایک تحلیلی مطالعہ : Critical Study of Objection Regarding Nabuwwat and Risalat of The Holy Prophet (May Allah Bless and Peace Be Upon Him) - Hussain, Dr Abrar (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2022)
ALLAH bestows Nabuwat upon the person who considers special worth and capable. ALLAH chooses only the person among his creation who is considered worthy of Nabuwat. Then He sent the chosen person with pure soul and nature so that Wahi could be revealed upon him according to the needs of human beings.That is why the Nabuwat and Risalat are not bestowed upon everybody. It is because when intends to create a prophet. He creates a man worthy of Nabuwat and filled with sheer innocence, purity, and virtue. As compared to a common man, a prophet has an additional blessing of Wahi. A common man perceives and predict through apparent event, senses, and wisdom but a prophet is bestowed with the ability to see and listen to the angles.